Écologie sociale et humanités numériques : intégrer la poésie à la science - Ada Desideri; Alexandre Détruit; Bianca Vallarano (Humanités Numériques)
This article proposes an ethical and political approach to the impact of digital humanities (DH) research, based on the philosophy of social ecology, in order to address the issue of degrowth in DH. Do DH have a role to play in a process of degrowth? How would an ecological DH project be organised? To address these questions, we will begin by summarising the principles of social ecology, as defined by Murray Bookchin, and their application to technology. We will then look at what it means to apply these principles to DH. Finally, we will present a digital publishing project based on these principles. We thus draw on the philosophy of social ecology, as well as on the concepts of degrowth, low-tech and minimal computing, to show that digital humanities can play a fundamental role in the development of an ecological digital environment, through a qualitative approach that values human creativity.